Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Discovery Learning di Kelas IV SD - Zakila Tahirrah; Arwin Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This study aims to describe the increase in the results of the study to use the model discovery learning on the integrated thematic learning. This research approach was qualitative and quantitative. Types of penelitianya are the PTK. Research conducted in Ulu Gadut 15 SDN Padang city. The techniques used are observation, test and non- test. Observational research results RPP cycle I with 78.12% percentage increase in cycle II becomes 96,87%. Aspects of teacher I cycle with the percentage of 84.37% increase in cycle II becomes 93,75%. Aspects of the learners I cycle with the percentage of 84.37% increase in cycle II becomes 93,75%. On the attitude of the people there are 8 I cycle and cycle II there are 8 learners had attitude stands out. Aspects of the knowledge cycle I with an average of 74 increased cycle II with an average of 85.25. Askill on spec I cycle with an average 80.28 increased cycle II with an average of 86.29. This proves a model of discovery learning can enhance the learning process and the learning outcomes learner.                                                                                                             Keywords: